قراءة في مفهوم الحداثة عند أدونيس - الدبو، أيسر محمد فاضل (جامعة الموصل - كلية الآداب, 2012)
يشكل الدرس الحداثوي اليوم فسحة تجول فيها الكثير من الشعراء دون أي عارض أو تيار يحد من حريتهم أو أفكارهم، فالحداثة التي حملت طبعة غريبة بامتياز، سمح لكثير من شعراء اليوم الدخول في عباءة الحداثة ووجدوا من خلالها طريقا سهلا للوصل إلى المجد فضلا عن كونها تمتلك قدار كافيا من الأفكار و الأطروحات التي رفعت المقياس الإبداعية التي عرف الشعر العربي على مدى قرون طويلة فكان أهم طروحاتها (قصيدة النثر) التي كان لها الدور الأكبر في أن يظهر كثير من الشعراء على الساحة الأدبية بلغة أقرب إلى اليومية وبموسيقى لا تحرك المشاعر وهي أقرب إلى تأملات العقل من القلب، ولعل الأقرب من الشعراء والمفكرين في الوقت نفسه هو (أحمد بن علي) الملقب بأدونيس الذي استثمر وبشكل واعي ودقيق هذه المعطيات... من هنا جاء هذا البحث ليعالج كيف استثمر عملاق الحداثيين اليوم هذه التقنيات وأخضعها على الفكر والأدب والثقافة. The Modernization lesson is regarded today as a place where many poets go around without any obstacle that reduces their freedoms and ideas. Modernization which carried a western attribute with excellence allowed many poets to access the garment of modernization as they found it an easy way to reach the glory. In addition to have enough capability of ideas and dissertations which raised the innovative measurement that the Arabic poetry lacked for many centuries, the most important thing of his achievements is (the Prose Poem) which had the greatest role of showing many poets in the Arab land with a language closer to the colloquial and with a music that the heart and brain refuse it. The most prominent of the poets and literary men is Ahmed bin Ali (named Odeneis) who invested these bits of information consciously and accurately. Thus, this paper came to tackle how the giant modernizer has invested these techniques and submitted it to ideology, literature and culture. The researcher has made stops at interpretations, ambiguity, signs, and symbols in order to analyze the ideology of Odeneis’s mind which could climb the ladder of peace and get high fame and reach the aim without looking at the means. Therefore, he mastered the art of playing with the word, dealt with it competently and invested the techniques of modernization when he has been the famous knight in the twentieth century until present time. This research reflects the extent to which Odeneis invested the term (modernization) from literary, ideological and cultural point of view and all the fields and types of knowledge.
Keywords: الإبداع الفني -- الحداثة -- الشعر العربي -- الصور اللغوية -- النقد الأدبي -- الشعراء العرب -- الفلسفة -- الفلاسفة العرب -- أدونيس -- العقل